2009
DOI: 10.1164/rccm.200812-1845pp
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Pulmonary Guidelines

Abstract: The natural history of cystic fibrosis lung disease is one of chronic progression with intermittent episodes of acute worsening of symptoms frequently called acute pulmonary exacerbations These exacerbations typically warrant medical intervention. It is important that appropriate therapies are recommended on the basis of available evidence of efficacy and safety. The Cystic Fibrosis Foundation therefore established a committee to define the key questions related to pulmonary exacerbations, review the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
229
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 646 publications
(249 citation statements)
references
References 65 publications
0
229
1
5
Order By: Relevance
“…The use of continuous infusion compared to intermittent infusion of beta-lactams in the treatment of APE remains a matter of controversy. In 2009, the CF Foundation (Bethesda, MD) concluded that there is insufficient evidence to recommend the first option (21). In 2011, Prescott et al evaluated the pharmacokinetics, efficacy, safety, stability, pharmacoeconomics, and quality-of-life effects of continuous-infusion antipseudomonal ␤-lactam therapy in patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…The use of continuous infusion compared to intermittent infusion of beta-lactams in the treatment of APE remains a matter of controversy. In 2009, the CF Foundation (Bethesda, MD) concluded that there is insufficient evidence to recommend the first option (21). In 2011, Prescott et al evaluated the pharmacokinetics, efficacy, safety, stability, pharmacoeconomics, and quality-of-life effects of continuous-infusion antipseudomonal ␤-lactam therapy in patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…In the final analysis, the authors concluded that there was no difference between the groups in treatment failure rate, changes in lung function, dyspnea, or bacterial density. Based almost entirely on these findings, the 2009 Cystic Fibrosis Foundation practice guidelines specifically stated that synergy testing should not be done in cystic fibrosis patients (25). This sentiment is certainly supported by a 2007 review claiming that synergy testing should not be performed in cystic fibrosis patients (26).…”
Section: Cystic Fibrosis and Synergy Testingmentioning
confidence: 99%
“…Acute pulmonary exacerbations and chronic infections due to Pseudomonas aeruginosa, Achromobacter xylosoxidans, and Stenotrophomonas maltophilia may result in decreases in pulmonary function and high morbidity and mortality rates among CF patients (3)(4)(5). It was shown that multidrug-resistant (MDR) P. aeruginosa strains were associated with accelerated progression of CF and unfavorable outcomes (6).…”
mentioning
confidence: 99%